PR3 Email Honeypot - ARGYROUDIS, PATROKLOS (My University, 2003)
Although there are different tools and technologies available to prevent attacks on privacy when online applications are used, few tools are available for detection of actions that violate privacy agreements. The loss of privacy when third parties obtain email addresses of users without their consent can be followed by unsolicited emails ? known as spam ? sent on the open communication channel. In this case, the loss of privacy is aggravated by the cost spent by people having to go through all these email messages. However, spam can also be used to detect Websites that default on their privacy policy by giving away private information, such as email addresses. If spam is received by an email address that has only been given to a single Website, we may conclude that this Website has either given the address to the spammer or very poor security. In either case, registration with that Website should be avoided. In this paper, we present a tool to detect such exchange of subscribers? private email addresses between online providers and to check whether these providers have respected their advertised privacy policies.
PUBLISHED
Keywords: Email, privacy, honeypot.